A Comparative Study on the Effect of the Voice of the Holy Quran and Arendeshine Music on the Anxiety of the Primiparous Women of the Natural Provisional Candidate - Kadkhodaei, Fatemeh; Mansouri, Ali; Hajar, Salehi; Abak, Fariba; Pour, Bahareh Khajeh; Nehbandani, Sanaz (Asian Journal of Pharmaceutical Research and Development, 2019)
Introduction and goal: Anxiety is the most common psychological reaction of pregnant women near childbirth and is a high prevalence in Iranian women. Nearly 50% of pregnant women report high levels of anxiety. The use of pharmaceutical methods to solve this problem has always led to problems and complications for patients. One of the non-pharmacological methods of music therapy. Therefore, the present study was conducted to compare the effects of the Voice of the Holy Qur'an and Arendeshine music on the anxiety of nulliparous women of normal delivery. Materials and Methods: The study population consisted of all pregnant women referred to the maternity hospital of Amiralmounin Hospital in Zabol city. The sample consisted of 54 female candidates of normal delivery, selected by convenience sampling and randomly divided into two groups. The data collection instrument was Spielberger's Standard Anxiety Inventory. At first, the questionnaire was completed by patients. Then, in the first intervention group Arend Stein, and in the second intervention group, the voice of the Quran was broadcast for 45 minutes and immediately after that the questionnaire was completed again. SPSS software version 22 was used to analyze the data. Findings: Findings showed that there was no significant difference between the mean of anxiety scores in the music group and the Qur'an before the intervention (p = 0.11). But after the intervention, this difference was significant (p = 0.02). Also, there was no significant difference between the mean scores of hidden anxiety in the two groups before the intervention (p = 0.21). But after the intervention, this difference was significant (p = 0.04). Discussion and conclusion: According to the results of this study, it can be concluded that the Qur'anic verse can be used as a non-pharmacological method in the treatment of anxiety in women who are candidates for delivery. Hence, employees are advised to use this method in conjunction with routine care.